P-P47 Impact of neoadjuvant chemotherapy on postoperative pancreatic fistula in patients undergoing pancreaticoduodenectomy. (16th December 2021) - Tanno, Lulu; Davies, Charlotte; Stevens, Claire; Fristedt, Richard; Arshad, Ali; Hamady, Zaed; Armstrong, Thomas; Primrose, John; Karavias, Dimitrios; Takhar, Arjun
Abstract: Background: Pancreatic adenocarcinoma (PDAC) is one of the most lethal tumours with a five-year survival rate of less than 7% for all stages. However, current evidence suggests neoadjuvant treatment (NAT) may have survival benefits in those with borderline resectable disease. Post-operative pancreatic fistula (POPF) is a potential complication after pancreaticoduodenectomy (PD) and is associated with long-term morbidity. The rate of developing POPF post-PD in those receiving NAT is currently unclear. Methods: Patients undergoing PD (both classical and pylorus-preserving) were identified from a prospectively collected local database. Those who received NAT prior to surgery were identified, and case-matched controls based on their age and sex, were then identified from the database. Post-operative drain amylase levels were used to compare POPF between groups. For the analysis, drain amylase levels greater than three times the upper limit of normal at day five were consistent with biochemical POPF. Results: A total of 34 patients (14 females, 20 males) underwent PD after receiving NAT at our unit from January 2013 to July 2021. The median age was 66 years at the time of surgery. Two patients (5.9%) in the NAC group had biochemical leaks on day five compared to 4 (11.8%) in the case-matched control group (p = 0.7). Conclusions: Our early data suggest a possibility of a lower incidence of biochemical POPF in those undergoing PD post-NAT. Aetiology on the development of POPD post-NAT is still unclear, and this requires further study and long-term follow up.